Motoneurons Dedicated to Either Forward or Backward Locomotion in the Nematode Caenorhabditis elegans - Haspel, Gal (Society for Neuroscience, 2010)
Multifunctional motoneurons and muscles, which are active during forward and backward locomotion are ubiquitous in animal models. However, studies in the nematode Caenorhabditis elegans suggest that some locomotor motoneurons are necessary only for forward locomotion (dorsal B-motoneurons, DB), while others (dorsal A-motoneurons, DA) are necessary only for backward locomotion. We tested this hypothesis directly by recording the activity of these motoneurons during semirestrained locomotion. For this purpose, we used epifluorescence imaging of the genetically encoded calcium sensor cameleon, expressed in specific motoneurons, while monitoring locomotor behavior through the microscope condenser using a second camera. We found that ventral and dorsal B-motoneurons (DB and VB) were coactive during forward locomotion while ventral A-motoneurons (VA) were only active during backward locomotion. The signals we recorded correlated with the direction of locomotion but not with the faster undulatory cycles. To our knowledge, these are the first recordings of motoneuron activity in C. elegans and the only direction-dedicated motoneurons described to date.